The complex link between NAFLD and type 2 diabetes mellitus — mechanisms and treatments - Targher, Giovanni; Corey, Kathleen E.; Byrne, Christopher D.; Roden, Michael (Nature reviews. Gastroenterology & hepatology, 2021)
Nonalcoholic fatty liver disease (NAFLD) has reached epidemic proportions worldwide. NAFLD and type 2 diabetes mellitus (T2DM) are known to frequently coexist and act synergistically to increase the risk of adverse (hepatic and extra-hepatic) clinical outcomes. T2DM is also one of the strongest risk factors for the faster progression of NAFLD to nonalcoholic steatohepatitis, advanced fibrosis or cirrhosis. However, the link between NAFLD and T2DM is more complex than previously believed. Strong evidence indicates that NAFLD is associated with an approximate twofold higher risk of developing T2DM, irrespective of obesity and other common metabolic risk factors. This risk parallels the severity of NAFLD, such that patients with more advanced stages of liver fibrosis are at increased risk of incident T2DM. In addition, the improvement or resolution of NAFLD (on ultrasonography) is associated with a reduction of T2DM risk, adding weight to causality and suggesting that liver-focused treatments might reduce the risk of developing T2DM. This Review describes the evidence of an association and causal link between NAFLD and T2DM, discusses the putative pathophysiological mechanisms linking NAFLD to T2DM and summarizes the current pharmacological treatments for NAFLD or T2DM that might benefit or adversely affect the risk of T2DM or NAFLD progression. This Review describes the evidence of an association and causal link between nonalcoholic fatty liver disease (NAFLD) and type 2 diabetes mellitus (T2DM), discusses their pathophysiological mechanisms and summarizes the pharmacological treatments that might benefit or adversely affect the risk of T2DM or NAFLD progression. Key points An updated meta-analysis of 33 observational studies showed that nonalcoholic fatty liver disease (NAFLD) is associated with an approximate doubled risk of type 2 diabetes mellitus (T2DM), irrespective of obesity and other metabolic risk factors. Patients with more advanced stages of liver fibrosis are at increased risk of T2DM; some observational studies have shown that improvement or resolution of NAFLD on ultrasonography is closely associated with a reduction of diabetes risk. NAFLD exacerbates hepatic and peripheral insulin resistance, predisposes to atherogenic dyslipidaemia and causes the systemic release of pro-inflammatory cytokines and hepatokines that can promote the development of T2DM. Treatment of NAFLD and T2DM is based on lifestyle modifications aiming at substantial weight loss in individuals with overweight or obesity. Although no pharmacotherapy is currently approved for NAFLD, some antihyperglycaemic drugs, such as pioglitazone, glucagon-like peptide 1 analogues and sodium–glucose cotransporter 2 inhibitors, have some efficacy. Multiple investigational compounds for NAFLD treatment, including modulators of bile acid and lipid metabolism, are in phase II and phase III randomized controlled trials.